2001
DOI: 10.1164/ajrccm.164.3.2010109
|View full text |Cite
|
Sign up to set email alerts
|

Airway Smooth Muscle Cell Proliferation Is Increased in Asthma

Abstract: asthma; human airway smooth muscle; cell culture; cell proliferation; hyperplasia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
379
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(413 citation statements)
references
References 17 publications
25
379
2
3
Order By: Relevance
“…It was considered that the inflammatory mediators and cytokines released by accumulated eosinophils in airway resulted in mucus hypersecretion, increased vascular permeability, bronchial hyperresponsiveness, smooth muscle contraction [19,20] . Furthermore, cytokines and growth factors released by inflammatory cells such as neutrophils are also involved in initiation of airway remodeling which is characterized by airway smooth muscle proliferation [21] . In this study, we investigated the therapeutic effect of rosiglitazone in OVA-induced asthma and possible mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…It was considered that the inflammatory mediators and cytokines released by accumulated eosinophils in airway resulted in mucus hypersecretion, increased vascular permeability, bronchial hyperresponsiveness, smooth muscle contraction [19,20] . Furthermore, cytokines and growth factors released by inflammatory cells such as neutrophils are also involved in initiation of airway remodeling which is characterized by airway smooth muscle proliferation [21] . In this study, we investigated the therapeutic effect of rosiglitazone in OVA-induced asthma and possible mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…Airway smooth muscle bundles were dissected free from surrounding tissues, and the cells were grown in culture at 37°C in a humidified 5% CO2 in air atmosphere, as previously described (10). Cells established in culture from each lung donor were checked for the presence of the airway smooth muscle contractile proteins ␣-smooth muscle actin and h-calponin by immunohistochemistry (12). At the time of plating, the average viability of each cell line was 96.2 Ϯ 1.1% (average Ϯ SE, n ϭ 11) as tested by trypan blue dye exclusion testing.…”
Section: Human Asmcmentioning
confidence: 99%
“…The first evidence for an intrinsic abnormality of ASM cells came from the observation that ASM cells from patients with asthma proliferate significantly faster than cells from control subjects (19). Indeed, a recent report demonstrated reduction of asthma symptoms and improved lung function after removal of ASM bundles (20).…”
Section: Bronchial Hyperresponsivenessmentioning
confidence: 99%
“…Compelling evidence now suggests that ASM plays an important role in regulating bronchomotor tone, in perpetuating airway inflammation, and in airway remodeling (32). Several publications have demonstrated that ASM, in addition to having contractile and proliferative properties, is also an important source of pro-inflammatory cytokines, chemokines and growth factors, as well as extracellular matrix components (19,35,36,42,43).…”
Section: Airway Inflammationmentioning
confidence: 99%